Morphophysiology of guava under saline water irrigation and nitrogen fertilization - Idelfonso L. Bezerra; Reginaldo G. Nobre; Hans R. Gheyi; Leandro de P. Souza; Francisco W. A. Pinheiro; Geovani S. de Lima (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The aim of this study was to evaluate the growth of grafted guava cv. ‘Paluma’ subjected to different concentrations of salts in irrigation water and nitrogen (N) fertilization. The plants were transplanted to 150 L lysimeters and under field conditions at the Science and Agri-food Technology Center of the Federal University of Campina Grande, in the municipality of Pombal - PB. The experiment was conducted in randomized block design in a 5 x 4 factorial scheme, with three replicates, and the treatments corresponded to five levels of electrical conductivity of irrigation water - ECw (0.3; 1.1; 1.9; 2.7 and 3.5 dS m-1) and four N doses (70, 100, 130 and 160% of the N dose recommended for the crop). The doses equivalent to 100% corresponded to 541.1 mg of N dm-3 of soil. Irrigation water salinity above 0.3 dS m-1 negatively affects the number of leaves, leaf area, stem diameter, dry phytomass of leaves, branches and shoots . A significant interaction between irrigation water salinity and N fertilization was observed only for the number of leaves and leaf area at 120 days after transplanting. N dose above 70% of the recommendation (378.7 mg N dm-3 soil) did not mitigate the deleterious effects caused by salt stress on plant growth.